Tinjauan Pelaksanaan Sistem Informasi Pendaftaran Rawat Jalan Menggunakan Metode PIECES di Fasilitas Kesehatan Tingkat Lanjut - Aida Nur Arrifah Aida; Nanik Setiyawati; Sumarah Sumarah (Journal of Health Information Management and Medical Record, 2025)
The Hospital Information System is a subsystem of the entire Hospital technique consisting of information processing used by individuals according to their roles. The use of this system supports patient care starting from outpatient registration to being processed as hospital reporting material by considering aspects of patient data security. Analyzing weaknesses in information systems can use the PIECES framework, namely Performance, Information, Economy, Control, Efficiency and Service. Purpose : Identifying the implementation of the information system based on the PIECES aspect in the Outpatient Registration section of Nyi Ageng Serang Kulon Progo Hospital. Methods : This study uses a qualitative descriptive method with a case study approach. Data was collected through interviews and observation. The research was conducted in April-May 2023. The research informants were 3 outpatient registration officers, 1 IT officer, and 1 head of medical records. Results: From the results of the study, information was obtained that the results of the performance aspect of the Information System were running according to user needs even though there were incomplete data items on general consent, the information aspect generated by the information system on information data according to user needs even though duplication of medical records is caused by the inconsistency of officers when inputting data; the economics aspect has not yet produced economic value because it is not completely paperless; the control aspect is already running with the control of access rights and security restrictions in the system using passwords and usernames; the efficiency aspect of the information system provides convenience in work; Information system service aspects can be relied upon because they provide convenience for users. Conclusion: Aspects of control, efficiency, service have been fulfilled. while in the performance aspect there are no general consent data items, the information aspect still occurs with double medical records, the economic aspect still has paper forms and medical record folder